Muhammadiyah’s Preaching Communication for the Religious Development of Farmers in Sinyonyoi Selatan Village, Kalukku District, Mamuju Regency. - Achir Akbar; Mahmuddin; Baharuddin Ali (Jurnal Mercusuar, 2022)
This research aims to understand the Muhammadiyah’s communication model of preaching towards religious development among the farming community and the community’s response to the applied preaching communication model by Muhammadiyah in enhancing the religious understanding of the farming community in the South Sinyonyoi Village, Kalukku Sub-District, Mamuju District. The research results indicate that Muhammadiyah’s communication model of preaching for religious development among the farming community in the South Sinyonyoi Village, Kalukku Sub-District, Mamuju District consists of three forms: first, preaching through sermons; second, lectures and discussions; and third, socialization. As for the community’s response to Muhammadiyah’s preaching communication model in enhancing the religious understanding of the farming community in the South Sinyonyoi Village, Kalukku Sub-District, Mamuju District, the community positively accepts Muhammadiyah’s preaching, leading to the effective implementation of the preaching activities. The community actively participates in and supports Muhammadiyah’s preaching efforts, subsequently leading to the enlightenment of the farming community and the abandonment of ritualistic practices associated with polytheism.